An unappreciated cell survival-independent role for BAFF initiating chronic lymphocytic leukemia - Ullah, Md Ashik; Garcillán, Beatriz; Whitlock, Eden; Figgett, William A.; Infantino, Simona; Eslami, Mahya; Yang, SiLing; Rahman, M. Arifur; Sheng, Yong H.; Weber, Nicholas; Schneider, Pascal; Tam, Constantine S.; et al. (Frontiers in Immunology, 2024)
Background Chronic Lymphocytic Leukemia (CLL) is characterized by the expansion of CD19+ CD5+ B cells but its origin remains debated. Mutated CLL may originate from post-germinal center B cells and unmutated CLL from CD5+ mature B cell precursors. Irrespective of precursor types, events initiating CLL remain unknown. The cytokines BAFF and APRIL each play a significant role in CLL cell survival and accumulation, but their involvement in disease initiation remains unclear. Methods We generated novel CLL models lacking BAFF or APRIL. In vivo experiments were conducted to explore the impact of BAFF or APRIL loss on leukemia initiation, progression, and dissemination. Additionally, RNA-seq and quantitative real-time PCR were performed to unveil the transcriptomic signature influenced by BAFF in CLL. The direct role of BAFF in controlling the expression of tumor-promoting genes was further assessed in patient-derived primary CLL cells ex-vivo. Results Our findings demonstrate a crucial role for BAFF, but not APRIL, in the initiation and dissemination of CLL cells. In the absence of BAFF or its receptor BAFF-R, the TCL1 transgene only increases CLL cell numbers in the peritoneal cavity, without dissemination into the periphery. While BAFF binding to BAFF-R is dispensable for peritoneal CLL cell survival, it is necessary to activate a tumor-promoting gene program, potentially linked to CLL initiation and progression. This direct role of BAFF in controlling the expression of tumor-promoting genes was confirmed in patient-derived primary CLL cells ex-vivo. Conclusions Our study, involving both mouse and human CLL cells, suggests that BAFF might initiate CLL through mechanisms independent of cell survival. Combining current CLL therapies with BAFF inhibition could offer a dual benefit by reducing peripheral tumor burden and suppressing transformed CLL cell output.